KONFLIK SOSIAL KEAGAMAAN DI DUSUN JAMBEWANGI KECAMATAN SEMPU BANYUWANGI - Fadilah, Iqbal; Wildan, Farhan; faisol , Ilham (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
The Muslim community of Jambewangi Hamlet, the existence of Nahdlatul Ulama and Muhammadiyah is a diversity that cannot be denied. However, religious understanding can taper potential conflicts, differences and religious doctrines can damage religious unity and harmony. Conflict can also damage the government system of Sempu village, especially if there is a person's personal interest. The purpose of this study is to determine the socio-religious conflicts in Jambewangi hamlet and find out the solution to the socio-religious conflicts in the hamlet. This type of research is qualitative. Data is obtained from primary and secondary data sources. Primary data include interview techniques, observation, and documentation as well as in-depth interviews. Secondary data are obtained from other sources that support and are considered relevant to the theme of study, such as books, journals, and so on. This study used Lewis A's conflict theory. Coser, and the data obtained in the field were studied using descriptive-interpretive techniques. In the results of the study, the conflict that occurred in Jambewangi Hamlet was a conflict between Nahdlatul Ulama and Muhammadiyah religious understandings, where there were several factors behind the conflict, including differences in the determination of qurban holidays, Ramadan Eid al-Fitr, differences in religious rituals, differences in political interests of certain individuals and so on., besides that there are also problems, namely the struggle for the territory of the place of worship, namely Al-Falah Mosque, then conflicts that occur in the political area occur in the election of the head hamlet. With the conflict unconsciously damaged the Jambewangi community system , thus it was very influential with the lives of the Jambewangi people. Conflict resolution carried out by the Head of Sempu Village to bridge with various social activities.